Agricultural landscapes in Costa Rica: forest remnants account for a rich mammal (Mammalia) community - Runnebaum, Maria I.; Spinola, Manuel R.; Arévalo, Edgardo; Rodríguez-Herrera, Bernal (Revista de Biología Tropical, 2025)
Introduction: The effects of habitat loss and fragmentation on wildlife are complex processes mediated by factors other than habitat size and isolation alone. For example, the quality of the surrounding matrix, edge-induced effects, and proximity to large forest tracks are of particular importance. These factors may allow or limit animal movements and, thus, population persistence in human-modified landscapes. This is the case in some remaining forest fragments in Costa Rican landscapes. Objective: To investigate the influence of the landscape composition on medium (< 10 kg) and large-sized (> 10 kg) terrestrial mammals thriving in an agricultural landscape, we surveyed mammal species in 30 sites in the Sarapiquí region, Costa Rica. Methods: We used 45 camera traps to assess the richness and composition of mammal species in forest fragments embedded in pineapple plantations and pastures from 2013 to 2014. Richness estimates were calculated using capture-recapture models for closed populations. We adjusted the models for repeated count data analysis to determine landscape cover types that best explained species richness. Results: Twenty-two species of mammals in nine orders and 16 families were recorded. Despite the habitat loss, fragmentation, and agricultural practice pressures over the years, the Sarapiquí region maintains a significant portion of its native mammalian fauna compared to comprehensive historical inventories available for the area. We found that forest cover best predicts the levels of species richness. Conclusion: many forest-dependent species, such as the threatened Baird’s Tapir, can thrive in fragmented habitats in agricultural landscapes, while other species seem to be heavily affected by habitat modification and land use type. Forested areas and pastures with a high density of scattered trees and proximity to extensive forests could enhance the conservation of mammal communities despite the intense human land use in these agricultural landscapes.